Somewhere (and nowhere) between modernity and tradition: towards a critique of international and indigenous perspectives on the significance of contemporary Chinese art - Gladston, Paul (Tate, 2014)
Reviewing international and indigenous perspectives on the significance of contemporary Chinese art, Paul Gladston argues for the necessity of new theoretical paradigms.